(untitled) (Pragyajyoti, 2021)
This paper studies the use of images in T. S. Eliot’s poem "The Love Song of J. Alfred Prufrock" so as to explore how the arrangement of images supports Eliot’s doctrine of objective correlative. It forwards the argument that the imagery portrays the speaker of the poem, Prufrock, as being one passing through mental alienation and procrastination, and establishes that the causes of his problems are industrialization, urbanization and ecological hazards. These problems are presented through the imagery, which, for the purpose of this paper, includes metaphors, similes, symbols, allusions, animation and personification as well. All the images, dug out and put together, reveal the deep irony which suggests Prufrock’s mental alienation